PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE TERHADAP PENGUNGKAPAN CSR PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Luh Mira Handayani; Komang Krishna Yogantara; Made Christin Dwitrayani (Journal Research of Accounting, 2021)
This study was conducted to determine the effect of firm size, profitability and leverage on CSR disclosure in manufacturing companies in Indonesia. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 with a total of 61 companies that meet the research criteria that have been set. The measurement of corporate social responsibility is based on the Global Reporting Index (GRI) version 4.0 category which is seen in the company's annual financial report. The research method used is quantitative research with data analysis using multiple linear regression analysis processed with the SPSS 25 statistical program. The results of this study indicate that CSR practices and disclosures as accounting coverage areas are significantly influenced by company size and company profitability. Leverage does not affect the company's CSR disclosures.